PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN DISIPLIN TERHADAP KINERJA KARYAWAN DI HOTELBOROBUDUR JAKARTA - Choirizal; Rivera P. Sukma (LPPM Universitas Asa Indonesia, 2019)
Purpose- This study aims is to determine the motivation, work environment and discipline effect partially or simultaneously to employee perfomance at Hotel Borobudur Jakarta. Design/methology/approach- The population in this study are employees of Hotel Borobudur Jakarta. The samples used in this study as many as 100 people,on probability sampling technique by purposesive due to lack of time and fund. The data collection from respondents using accidental technique. Methods of data analysis used in this study is to test the validity, reliability test, classic assumption test (normality test, multicollinearity, heteroscedasticity test and linearity test). While testing the hypothesis includes the F-test, t test and partial correlation analysis and the coefficient of determination (R²). Findings- Motivation variable, work environment and discipline variable have the significant effect on the employee perfomance either partially or simultaneously.